(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Effective teamwork between operations and anesthesia technicians is essential for the smooth functioning of the operating room (OR) and the delivery of high-quality patient care. This article explores the pivotal roles of operations and anesthesia technicians in the OR, highlighting their responsibilities, challenges, and strategies for optimizing collaboration. Through a synergistic approach, operations technicians prepare the surgical suite and assist the surgical team, while anesthesia technicians monitor patients’ vital signs and ensure their safety under anesthesia. Despite challenges such as time constraints and equipment malfunctions, open communication and mutual respect foster teamwork and enhance preparedness for various scenarios encountered in the OR. By recognizing the importance of collaboration and investing in strategies to enhance teamwork, healthcare facilities can improve the quality and safety of surgical care.